FOSSILISATION IN PROFESSIONAL DEVELOPMENT (A Case Study atSMPN 1 Subang) - SRI SURYANTI (FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN, 2016)
Toimprove the professionalism of teachers the government through the Minister of State for Administrative Reform Bureaucracy No. 16 Year 2009 proposed the regulation in functional title teacher and figures credit. Continuing professional developmentis the development of teacher competenciesare implemented according tothe needs, gradual, sustained to enhance professionalism. This activities can be done through education and training or through collective functional teacher. Therefore, the teachers of Mathematics, Science and ICT in SMP Negeri 1 Subang need to improve their competencies in English so that the schools provide the program of professional development for them. This study is aimed to discovery the teacher’sfossilisation in professional development. A case study will be used in this study and the data will be gathered from multiple sources in natural setting; the interviews with participants, participant learning, and the result of TOEIC.Expected finding in this study is whether the teachers of Mathematics, Science, and ICT can resolvefossilisation in professional development.